Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-018-37917-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Approach of Intrinsically Disordered CIP/KIP Proteins

Abstract: The mammalian CIP/KIP family proteins are intrinsically disordered proteins (IDPs) that can regulate various cellular processes. However, many reports have shown that IDPs generally evolve more rapidly than ordered proteins. Here, to elucidate the functional adaptability of CIP/KIP proteins in vertebrate, we analysed the rates of evolution in relation to their structural and sequence properties and predicted the post-translational modification based on the sequence data. The results showed that CIP/KIP protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Long consecutively disordered residues (>30) may function as entropic chains or can be involved in interactions using combinations of recognition motifs or domains [33]. We previously reported that residues within disordered regions that function as entropic chains evolve quickly, whereas those involved in protein-protein interactions tend to be constrained [13,14]. Thus, it may be relevant for some ancient glycoside hydrolases to harbour long stretches of disordered regions because the conformational plasticity of these regions enables the recognition of or binding to multiple partners, which is beneficial for identifying misfolded proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long consecutively disordered residues (>30) may function as entropic chains or can be involved in interactions using combinations of recognition motifs or domains [33]. We previously reported that residues within disordered regions that function as entropic chains evolve quickly, whereas those involved in protein-protein interactions tend to be constrained [13,14]. Thus, it may be relevant for some ancient glycoside hydrolases to harbour long stretches of disordered regions because the conformational plasticity of these regions enables the recognition of or binding to multiple partners, which is beneficial for identifying misfolded proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by comparison of evolutionary rates between ordered and disordered structured proteins. Disordered regions commonly evolve faster than ordered structures [10][11][12][13][14] because of differences in the relative constraints that maintain folding interactions [15]. However, there are exceptions to this rule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexible disorder has a constrained disordered structure despite having rapid evolution of residues; the amino acid substitutions of this property are constrained to residues that confer structural flexibility as the change from structurally disordered to ordered could affect protein function. This type of IDR typically functions as an entropic spring, flexible linker, or spacer without becoming structured and is frequently located outside the domain region [26,[35][36][37]. In contrast, constrained disorder is associated with protein-protein interaction interfaces that adopt a structured conformation or undergo folding upon binding and are thus constrained in terms of sequence, while still requiring flexibility.…”
Section: Rate Of Evolution Per Site In Rtt-causing Proteinsmentioning
confidence: 99%
“…Disordered regions commonly evolve faster than ordered structures [10][11][12][13] because of differences in the relative constraints that maintain folding interactions [14]. However, there are exceptions to this rule.…”
Section: Introductionmentioning
confidence: 99%